THE DESIGN AND FUNCTIONAL ORGANIZATION OF MULTI-PURPOSE SPACES IN LUXURY RESORT HOTELS - Borysenko А.S.; Naili, Bouchra; Hdidouch, Rida (Municipal economy of cities. Series: «Economy science», 2025)
The article explores multi-purpose spaces in luxury hotels, emphasizing guest experience and efficiency. Key design principles include flexible layouts, smart technology, and biophilic elements. Real-world examples classify strategies by spatial typology, highlighting adaptability in response to evolving hospitality trends.